2019
DOI: 10.3390/gels5040047
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline and Monocaprin In Situ Hydrogel: Effect on Stability, Mucoadhesion and Texture Analysis and In Vitro Release

Abstract: The aim of this study was to develop a stable aqueous formulation containing a combination of doxycycline and monocaprin in clinically relevant concentrations. Increase in expression of Matrix metalloproteinases (MMPs) and microbial role in oral diseases is well established and the combination of above active ingredients could be potentially beneficial in treatment of oral mucosal conditions. The hydrogels containing different concentrations of doxycycline and monocaprin in the presence and absence of stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 38 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…In our study, the hardness values were found to be ideal, and it was determined that the hardness of the formulation containing Aloe vera was lower than the formulations which Aloe vera was not added (Figure 3). The adhesion parameter is established as the work required to overcome the attractive forces between the surface of the sample and the probe [51]. This parameter is related to the adhesive characteristics of the formulation; higher adhesion value provides more adhesion on the tissue surface, and this improves the desired retention time of the drug [49].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the hardness values were found to be ideal, and it was determined that the hardness of the formulation containing Aloe vera was lower than the formulations which Aloe vera was not added (Figure 3). The adhesion parameter is established as the work required to overcome the attractive forces between the surface of the sample and the probe [51]. This parameter is related to the adhesive characteristics of the formulation; higher adhesion value provides more adhesion on the tissue surface, and this improves the desired retention time of the drug [49].…”
Section: Resultsmentioning
confidence: 99%
“…Cohesion is defined as the internal structural strength that maintains strong interconnections with a certain level of resistance to rupture during application [50]. It is defined as the structural deformation and strength of the internal bonds in the sample after shear stress [51,52]. Adhesion and cohesion values are high in F5 gel and lower in A21 gel.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of saliva, existing dosage forms are often unable to adhere stably to the site of the lesion or be dissolved. Swallowing may result in the loss of dissolved or suspended drugs, leading to involuntary removal of dosage forms or even suffocation 86,87 . The emergence of hydrogels solves the shortcomings above and makes it possible for local treatment of oral mucosal adhesion with the inherent charge, hydrogen bond, ionic bond or covalent bond on polymer chain 88 .…”
Section: Treatment Of Oral Mucosal Diseasesmentioning
confidence: 99%
“…Swallowing may result in the loss of dissolved or suspended drugs, leading to involuntary removal of dosage forms or even suffocation. 86,87 The emergence of hydrogels solves the above shortcomings and makes it possible for local treatment by oral mucosal adhesion through the inherent charge, hydrogen bond, ionic bond or covalent bond on the polymer chain. 88 The components are simply diffused in situ , or separated from hydrogels by polymer–drug interaction and stimulus response to achieve controlled local release of the drug at the infected site.…”
Section: Oral Mucosa and Skin Carementioning
confidence: 99%
“…Oxidative degradation is enhanced by exposure to water molecules, light or elevated temperature. Studies have shown that using antioxidants to prevent oxidative degradation was ineffective; therefore, different approaches are needed to increase stability of doxycycline [ 7 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%